Corona Virus Pandemic Impact on Sales Revenue of Micro Small and Medium Enterprises (MSMEs) in Pekalongan City, Indonesia - Milzam, Muhammad; Mahardika, Aditia; Amalia, Rizka (Vocational College of Universitas Diponegoro, 2020)
This study aims to determine the impact of the covid-19 pandemic on the sales revenue of Micro Small and Medium Enterprises (MSMEs) in Pekalongan City. The data collected from surveys are sales revenue before and after Corona virus Pademic starting from the enactment of social distancing rules (March 16 2020 until 16 April 2020). The analysis carried out in the form of data analysis and descriptive data analysis. Based on 282 SMEs units sampled, it was found a decrease in total sales revenue of 53.5%. The type of business that has the greatest reduction in revenue sales is the fashion business. The corona virus pandemic has an economic impact to the community, especially to the Micro Small and Medium Enterprises (MSMEs) in Pekalongan City. This research is expected to be a policy reference for the local governments to deal with the economic crisis caused by the corona virus pandemic.